A novel low-temperature resistive NO gas sensor based on InGaN/GaN multi-quantum well-embedded p–i–n GaN nanorods. Issue 4 (4th January 2019) - Reddeppa, Maddaka; Park, Byung-Guon; Chinh, Nguyen Duc; Kim, Dojin; Oh, Jae-Eung; Kim, Tae Geun; Kim, Moon-Deock
Abstract : In gas sensors, metal oxide semiconductors have been considered as favorable resistive-type toxic gas sensing materials. Abstract : In gas sensors, metal oxide semiconductors have been considered as favorable resistive-type toxic gas sensing materials. However, the higher temperature operation of metal oxides becomes a barrier for their wide range of applications in explosive and flammable gas environments. In this regard, great efforts have been devoted to reducing the operating temperature of the sensor. We demonstrated a chemical resistor-type NO gas sensor based on p–i–n GaN nanorods (NRs) consisting of InGaN/GaN multi-quantum wells (MQW). The sensor exhibited superior NO gas sensing performance to p-type GaN NRs. Furthermore, it also showed a remarkably improved response and fast recovery under UV irradiation ( λ = 367 nm) of different UV intensities (7 to 20 mw cm −2 ) under reverse bias. The sensing performance of MQW-embedded p–i–n GaN NRs was enhanced with the boosted response by 4-fold at 35 °C under UV irradiation. The significant decrease in the resistance of the sensor under UV irradiation was mainly due to the extraction of photo-generated carriers under reverse bias, which can enhance the ionization of oxygen molecules. In addition, the effect of relative humidity (30%–60%) on the gas sensing performance was also manifested in this study. The selectivity of the sensor was determined by using other gases (NO, NO2, O2, NH3, H2 S, CO, and H2 ), which exhibited a low response towards all tested gases other than NO. The experimental results demonstrated that p–i–n GaN NRs with InGaN/GaN MQW is a promising material for the detection of NO gas. Specific emphasis was laid on the enhanced response of p–i–n GaN NRs in reverse bias under UV irradiation.